College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter 4 - Section 4.2 - Exponential Functions - 4.2 Exercises - Page 409: 24


See the picture below.

Work Step by Step

By calculating a few pairs, plotting the ordered pairs, and connecting the dots on the graph with a smooth curve, we graph the function. By the laws of exponents: $(\frac{1}{a})^{-x}=a^{x}$. We transform the function to: $f (x)=(\frac{1}{6})^{-x}=6^x$ because it's easier to calculate with this form. A few pairs: $f(-1)=6^{-1}=\frac{1}{6}$ $f(0)=6^0=1$ $f(1)=6^1=6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.